Voltage-Gated Ca2+ Channels in Dopaminergic Substantia Nigra Neurons: Therapeutic Targets for Neuroprotection in Parkinson's Disease? - Ortner, Nadine J. (Frontiers in Synaptic Neuroscience, 2021)
The loss of dopamine (DA) producing neurons in the Substantia Nigra pars compacta (SN) underlies the core motor symptoms of the progressive movement disorder Parkinson’s disease (PD). To date, no treatment to prevent or slow SN DA neurodegeneration exists, thus, the identification of the underlying factors contributing to the high vulnerability of these neurons represents the basis for the development of novel therapies. Disrupted Ca2+ homeostasis and mitochondrial dysfunction seem to be key players in the pathophysiology of PD. The autonomous pacemaker activity of SN DA neurons, in combination with low cytosolic Ca2+ buffering, leads to large somatodendritic fluctuations of intracellular Ca2+ levels that are linked to elevated mitochondrial oxidant stress. L-type voltage-gated Ca2+ channels (LTCCs) contribute to these Ca2+ oscillations in dendrites, and LTCC inhibition was beneficial in cellular and in vivo animal models of PD. However, in a recently completed phase-3 clinical trial, the dihydropyridine (DHP) LTCC inhibitor isradipine failed to slow disease progression in early PD patients, questioning the feasibility of DHPs for PD therapy. Novel evidence suggests that also R- and T-type Ca2+ channels (RTCCs, TTCCs) represent potential PD drug targets. This short review aims to (re)evaluate the therapeutic potential of LTCC, RTCC and TTCC inhibition in light of novel preclinical and clinical data, and the feasibility of available Ca2+ channel blockers to modify PD disease progression. I also summarize their cell-specific roles for SN DA neuron function and describe how their gating properties allow activity (and thus their contribution to stressful Ca2+ oscillations) during pacemaking.